2022
DOI: 10.18488/61.v10i4.3224
|View full text |Cite
|
Sign up to set email alerts
|

A Second Order Confirmatory Factor Analysis of the Digital Transformation for a Distance Education Institution

Abstract: In the current times, very little attention is paid on measuring the performance of digital transformation in educational institutions so that it can run sustainably. This study aimed to create an appropriate instrument in measuring digital transformation in educational institutions, especially distance education institution. The study used a quantitative approach and collected data from 402 Universitas Terbuka students of 5 faculties; the Faculty of Economics (FE), Faculty of Law, Social and Political Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is very effective because even though the number of students is vast, they seem to be treated individually by the teacher (Xin, Katuk, & Arif, 2021). Communication tools developed using web-based learning include discussion forums and chat rooms (Devine, Bourgault, & Schwartz, 2020;Khurniawan, Irmawaty, & Erda, 2022;Swaramarinda, Isa, Yusof, Kadir, & Rahman, 2022;Syafi'i, 2020;Tjilen et al, 2018). Students can ask the teacher and their peers' questions directly with a quick response.…”
Section: Technology Integrated With Web-based Learningmentioning
confidence: 99%
“…This is very effective because even though the number of students is vast, they seem to be treated individually by the teacher (Xin, Katuk, & Arif, 2021). Communication tools developed using web-based learning include discussion forums and chat rooms (Devine, Bourgault, & Schwartz, 2020;Khurniawan, Irmawaty, & Erda, 2022;Swaramarinda, Isa, Yusof, Kadir, & Rahman, 2022;Syafi'i, 2020;Tjilen et al, 2018). Students can ask the teacher and their peers' questions directly with a quick response.…”
Section: Technology Integrated With Web-based Learningmentioning
confidence: 99%
“…DT is an important technical means for the application of ECP. The application of DT has promoted the establishment of ECP and the optimization and improvement of ECP [7]. Data processing and intelligent computing can be performed through DT in ECP.…”
Section: Related Workmentioning
confidence: 99%
“…Research related to the digital transformation indicators in Universitas Terbuka has been carried out by Khurniawan et al, (2022). Based on this research, it was found that strategy and institutional governance, curriculum and delivery methods, assessment, staff support and professional development, and infrastructure and resources are indicators of digital transformation that digital transformation is appropriate to measure the digital transformation at the Open University.…”
Section: Introductionmentioning
confidence: 99%